2022
DOI: 10.1002/jctb.7031
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of perchlorate by cationic modified adsorbent in a fixed bed continuous flow column

Abstract: BACKGROUND: In the present investigation, rice husk modified by Cetyltrimethylammonium bromide (CTAB) was used for the adsorptive removal of perchlorate by fixed column experiments from aqueous solution. The performance of the cationic modified rice husk (MRH) was characterized by Fourier transform infrared analysis. Experiments were carried out in a properly designed test rig consisting of a fixed-bed column of the cationic MRH with provision for admitting variable flow rates of the adsorbate at specified con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Some works showed that calcining rice husks at 500°C for 1 hour increased the adsorption of basic dyes. Rice husks modi ed with CTAB (Cethyltrimethylammonium bromide ) have been used to remove Congo Red, Methyl Orange, and perchlorate ions [18,22,23]. Raw rice husks and CTAB-modi ed rice husks have also been used for the adsorption of ammonium and nitrate ions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Some works showed that calcining rice husks at 500°C for 1 hour increased the adsorption of basic dyes. Rice husks modi ed with CTAB (Cethyltrimethylammonium bromide ) have been used to remove Congo Red, Methyl Orange, and perchlorate ions [18,22,23]. Raw rice husks and CTAB-modi ed rice husks have also been used for the adsorption of ammonium and nitrate ions [24].…”
Section: Introductionmentioning
confidence: 99%